2014
DOI: 10.1177/0272431614529365
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Ups and Downs of Mathematics Engagement in the Middle Years of School

Abstract: This study of 1,601 students in the middle years of schooling (Grades 5-8, each student measured twice, 1 year apart) from 200 classrooms in 44 schools sought to identify factors explaining gains and declines in mathematics engagement at key transition points. In multilevel regression modeling, findings showed that compared with Grade 6 students (upper elementary; the reference category), students in Grades 7 (typically the first secondary school year) and 8 have significantly declined in mathematics engagemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 85 publications
(140 reference statements)
3
70
0
1
Order By: Relevance
“…Achievement was assessed by a post‐survey test of numeracy and literacy. The numeracy and literacy items comprised a set of mathematics, spelling, and comprehension test questions arranged in order of difficulty and adapted from Martin, Anderson, Bobis, Way, and Vellar () and Martin, Way, Bobis, and Anderson () along the lines of the Wide Range Achievement Test (WRAT, Wilkinson, ) so as to be applicable to a range of age groups. Indeed, the test was sensitive to significant graduated mean‐level differences for each year level, F (2, 417) = 8.23, p < .001, leading to standardization by year level.…”
Section: Methodsmentioning
confidence: 99%
“…Achievement was assessed by a post‐survey test of numeracy and literacy. The numeracy and literacy items comprised a set of mathematics, spelling, and comprehension test questions arranged in order of difficulty and adapted from Martin, Anderson, Bobis, Way, and Vellar () and Martin, Way, Bobis, and Anderson () along the lines of the Wide Range Achievement Test (WRAT, Wilkinson, ) so as to be applicable to a range of age groups. Indeed, the test was sensitive to significant graduated mean‐level differences for each year level, F (2, 417) = 8.23, p < .001, leading to standardization by year level.…”
Section: Methodsmentioning
confidence: 99%
“…A plethora of empirical studies have suggested a number of motivational and social antecedents that could encourage and cultivate students' proactive engagement. Motivational antecedents include, for example, self-efficacy (e.g., Breso et al, 2011;Phan, 2014c;Phan & Ngu, 2014a;Ouweneel et al, 2013;Reeve & Lee, 2014;Phan, 2014b;Wang & Eccles, 2013), task value (e.g., Wang & Eccles, 2013;Martin, Way, & Anderson, 2015;Phan & Ngu, 2014b;Fan, 2011), and mastery goal orientation (e.g., Wang & Holcombe, 2010;Reeve & Lee, 2014;Phan, 2014a;Gonida, Voulala, & Kiosseoglou, 2009). In addition, empirical findings have produced salient social antecedents of engagement that include, for example, parents' and teachers' support (e.g., Perry, Liu, & Pabian, 2010;Wang & Holcombe, 2010;Wang & Eccles, 2013;Brewster & Bowen, 2004;Wang & Eccles, 2012b;Estell & Perdue, 2013).…”
Section: In Totalitymentioning
confidence: 99%
“…Until recently, much of the research on engagement in math and science learning has focused on mean-level gender differences in motivation, engagement, and contextual factors. Although girls and boys have similar math and science course grades, several studies have shown that girls have lower perceptions of their abilities in these domains than do boys (Andre, Wingham, Hendrickson, & Chambers, 1999;Marsh, Trautwein, L€ udtke, K€ oller, & Baumert, 2005;Watt et al, 2012). Additionally, there is evidence that girls have less positive attitudes toward science, less interest in the domain, and are more likely to perceive science as difficult (Brotman & Moore, 2008;Jones, Howe, & Rua, 2000;Miller, Blessing, & Schwartz, 2006;Wang, 2012).…”
Section: Gender and Engagementmentioning
confidence: 99%
“…Adolescents’ engagement in math and science coursework is critical for developing the preparation and persistence necessary to pursue college majors and careers in science, technology, engineering, and mathematics (STEM) fields (Maltese & Tai, ). Unfortunately, American adolescents’ engagement in math and science declines over the middle and high school years, particularly for female and minority students (Martin, Way, Bobis, & Anderson, ; Wigfield et al, 2015). As a result, many American youth fail to attain the fundamental math and science skills that would enable them to successfully participate in the workforce (Baldi et al, ; Evan, Gray, & Olchefske, ), and even fewer attain the advanced knowledge and abilities needed to pursue STEM careers (National Science Foundation, ).…”
mentioning
confidence: 99%